The Influence of Organizational Communication to Employee Performance of Administrative Assistant for Economic and Development Secretariat of Bandung - Ony Djogo (SAMPURASUN, 2018)
The research was conducted to analyze the influence of Organizational Communication to employee performance, develop theories and concepts of Organizational Communication and performance along with its aspects and apply the theory of Organizational Communication in solving the problems of employee performance of Administrative Assistant for Economic Affairs and Development of Regional Secretariat in Bandung. This research applies explanatory survey method with a quantitative approach. The variables are consisted of Organizational Communication (X) and Employee Performance (Y). Communication organization consists of the main forms of communication-down (X1), upward communication (X2) and horizontal communication (X3). They are very strong in the performance of employees that derives from dimensions in quantity of work, quality of work, job knowledge, creativeness, cooperation dependability, initiative and personal quantity. The sample is taken by using census techniques. The respondents are the employees of the Administrative Assistant for Economic and Regional Development Secretariat of Bandung as many as 112 employees. The technique of data analysis uses path Analyisis. The data are analyzed quantitatively by using statistical correlation and path analysis with SPSS 21 to see the value of the standard Beta regression test results. The result showed that communication of organizational influences the performance of employees in the Administrative Assistant for Economic and Regional Development Secretariat in Bandung is determined by the primary form of communication downward, upward communication and horizontal communication which are acceptable. Organizational Communication simultaneous influence on employee performance with a total effect of 58.6%, while the remaining 41.4% is influenced by other variables was not examined. Partially downward communication, upward communication and horizontal communication affected the performance of employees with a total effect of respectively 49.2%, 7.6% and 1.72%.